Antioxidant treatment ameliorates phenotypic features of SMC1A-mutated Cornelia de Lange syndrome in vitro and in vivo. (30th May 2018) - Cukrov, Dubravka; Newman, Trent A C; Leask, Megan; Leeke, Bryony; Sarogni, Patrizia; Patimo, Alessandra; Kline, Antonie D; Krantz, Ian D; Horsfield, Julia A; Musio, Antonio
Abstract: Cornelia de Lange syndrome (CdLS) is a rare disease characterized by cognitive impairment, multisystemic alterations and premature aging. Furthermore, CdLS cells display gene expression dysregulation and genomic instability. Here, we demonstrated that treatment with antioxidant drugs, such as ascorbic acid and riboceine, reduced the level of genomic instability and extended the in vitro lifespan of CdLS cell lines. We also found that antioxidant treatment partially rescued the phenotype of a zebrafish model of CdLS. Gene expression profiling showed that antioxidant drugs caused dysregulation of gene transcription; notably, a number of genes coding for the zinc finger (ZNF)-containing Krueppel-associated box (KRAB) protein domain (KRAB-ZNF) were found to be downregulated. Taken together, these data suggest that antioxidant drugs have the potential to ameliorate the developmental phenotype of CdLS.